Revealing User Perception and Mental Model in My Tel-U Apps: A UX and Integrated Method - Muttaqin, Alif Noorachmad; Lubis, Muharman; Handayani, Dini; Zamzami, Ikhlas Fuad (Applied Information System and Management (AISM), 2025)
My Tel-U app user experience and usability were tested using a mixed-methods design with both quantitative and qualitative measurements. User experience was measured quantitatively using the User Experience Questionnaire (UEQ), as well as general satisfaction assessed by the Customer Satisfaction Score (CSAT), and task-based usability testing to evaluate actual user interaction. Thirty participants from different faculties and levels of study at Telkom University joined to experience various digital exposures and acclimate their behaviour to the application. UEQ results indicate overall positive attitudes across all six scales, with Perspicuity, Attractiveness, and Dependability achieving the highest scores. CSAT was 90%, indicating that most users were satisfied or very satisfied with the application. Although task accomplishment increased, usability testing revealed that problems such as slowness, poor navigation organization, and inadequate system feedback persisted. Open-ended questions confirmed similar issues, such as core functionality like grade viewing and attendance tracking, as well as ongoing concerns about performance and reliability. These results indicate that, although the application adheres to functional requirements, user support, response time, and clarity may need improvement in certain aspects. This research contributes to an integrative UX evaluation model by incorporating perceptual, emotional, and behavioural measures. The results provide positive feedback to developers and institutional stakeholders, justifying priorities for alterations that will make the My Tel-U app more accessible, user-friendly, and support long-term usage on the online learning platform.